The adoption of National Green Procurement Plans from the perspective of circular economy - Marian Siminică; Marioara Avram; Luminița Popescu; Roxana Loredana Avram (Amfiteatru Economic Journal, 2020)
The tendency of depletion of non-renewable resources and the environment's continuous degradation have been considered in the last centuries acceptable as side effects for achieving the economic growth and satisfying the human needs in the conditions of demographic growth following an upward trend. An adequate response to all these challenges is related to increasing the share of green GDP in total GDP, to green procurement and to the large-scale promotion of circular economy. At EU level, there are appropriate legislation and programs and packages aimed at implementing green procurement and the circular economy. There are also prize-winner countries that have adopted National Green Procurement Plans before they became mandatory, countries that have found it harder to adopt this type of plans, but also countries that have not adopted National Green Procurement Plans such as Estonia, Greece, Hungary, Luxembourg and Romania. The article focuses on an analysis of the impact of national green procurement plans adoption on circular economy in the European Union member states for the period 2007-2018, with the help of an unrestricted VAR panel (PVAR), based on three hypotheses according to which the impact of these plans' adoption is positive on economic growth, CO2 emissions and circular economy. Data taken from Eurostat and processed using E-Views 9 econometric software allowed the validation of research hypotheses, confirming the positive impact of the adoption and implementation of green procurement national plans on some significant indicators characterizing the circular economy, which is likely to encourage the generalization of concerns regarding the adoption of coherent public policies in all Member States.
Keywords: F64; O13; Q28; 330; green GDP; green procurement; circular economy; waste; recycling